ANALISA PUTUSAN MAHKAMAH KONSTITUSI NO. 97/PUU-XIV/2016 TERKAIT PENCANTUMAN ALIRAN KEPERCAYAAN PADA KOLOM AGAMA KARTU TANDA PENDUDUK DAN KARTU KELUARGA - Nugroho, Faiz Ridho; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
This study aims to find out whether the judicial panel’s judgment on the decision of the Constitutional Court No.97 / PUU-XIV / 2016 has been in accordance with the principles of the laws and regulations in force in Indonesia. At the dogmatic level of law, something is a legal issue if the matter relates to the relevant legal provisions and facts faced. reviewed from the legal facts of the inclusion of the traditional belief in the religious columns of the Civil Identity Cards and Civil Family Cards in the demographic administration law; and the arrangement of religion and the flow of trust in the laws and regulations.This research is prescriptive where in view of its purpose, this research includes normative or doctrinal law research. The sources of legal materials used in this study are primary legal materials, secondary law materials and non-law materials. Technique of collecting data used is study of document or book material and interview. Data analysis technique used is deductive.The results of the study show that the verdict of the Constitutional Court No.97 / PUU-XIV / 2016 relating to the traditional beliefs in the columns of religious civil identity cards and civil family cards has not been in accordance with the principles of the 1945 Constitution and existing legislation.